KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - inne Aryanti; Farida Titik Kristanti; Hendratno H (JRAK, 2017)
The purpose of this research is to understand the influence of institutional ownership, managerial ownership, and audit quality for earnings management. The unit analysis in this research is the report of a finance company sub sector coal listed Indonesia Stock Exchange. The sampling technique of this research is used by purposive sampling and obtained 8 sub-sector coal companies in 20122015 to obtain 32 samples as observation material. Methods of data analysis in this research is panel data regression. The results showed that institutional ownership has no significant effect on earnings management, while managerial ownership influence significantly the negative direction and quality of the audit significant influence with a positive direction to earnings management so for investors should choose a company with a large managerial ownership and due attention to the quality of KAP being an independent auditor of a company that does not take the wrong investment decisions.